PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR KOMPLEKS DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA SISWA KELAS X IPA 1 SMA NEGERI 1 KOTA SORONG - Tri Harjanti (LPPM Politeknik Saint Paul Sorong, 2018)
The main reason in research about complex procedural text because this text is used in daily life. Background in this research caused the result of complex procedural text which is reached by the students is very low, so that the writer and collaborator want to increase the skill in writing complex procedural text by using series picture media. This research purpose is describing about complex procedural text, using series picture media of science students grade x IPA 1 SMA N I Sorong, this research is class activity research. The research is done 2 cycles, every cycle is consisted (1) planning activity, (2) doing the activity, (3) observation, (4) reflection. The research subject is students grade x IPA 1, SMA N Kota Sorong. Data resources are from teacher’s information’s, students, partner, and student’s data’s, the technique of collecting data are collected using test technique, observation, and student’s data’s and interview. Data analysis that is used is quantitative and qualitative analysis data technique. The studying with using series picture can increase the skill of writing complex procedural text. The level of skill writing complex procedural text at cycle I: 26,31% increase to: 94,73% in cycle II. The using of series picture media studing can be facility to increase the student’s ability in writing complex procedural text